CORRELATION BETWEEN ALCOHOL CONSUMPTION AND THE SOCIO-ECONOMIC PROFILE OF RURAL ADOLESCENTS (Fiep Bulletin - online, 2014)
The purpose of this study was to verify alcohol consumption indexes among adolescent  students attending high school of Public Educational Institutes in Lapa-PR municipal rural district, as well as to identify possible differences between boys' and girls' alcohol consumption and differences in the consumption pattern as they grow older during adolescence, and also to investigate the  relation between alcohol consumption and socio-economic profile. The sample was composed by 193 adolescents between the ages of 14 and 20, 101 males and 92 females, high school students in the 1st. to the 3rd. year of Lapa-PR municipal rural district. The consumption of alcohol was measured through the Alcohol Use Disorders Identification Test (AUDIT). The Brazil Economical Classification Criterion was used (CCEB) to evaluate the participants' socio-economic profile. For the data analysis the Kruskal-Wallis test was used to verify possible differences in alcohol consumption among the age groups. The Mann-Whitney test was used to analyze the differences between male and female alcohol consumption and Spearman's Correlation to investigate the relationship between alcohol consumption and the adolescents' socio-economic profile, and the significance level was fixed of p
Keywords: Alcohol consumption; socio-economic profile; adolescent